Designing and sewing special occasion dresses with Patchwork from Juan Tani fabrics - Banlengloi, Waraporn; Buenae, Mafusoh; Muzayee, Orathai; senadee, Kanyarat (Journal of Home Economics Technology and Innovation, 2022)
The purpose of this study was to design and Sewing special occasion dresses using Patchwork from Juan Tani fabric. and surveyed the satisfaction of special occasion dresses with fabric cutting techniques from Juan Tani fabrics from a specific sample Only 50 people. who love Juan Tani fabric. The research instrument was an online questionnaire. Data were analyzed by using frequency, percentage and mean. Research findings on design and sewing of occasion dresses using from Juan Tani fabrics which are 5 prototype sets. satisfaction survey results It was found that most of the respondents were female, aged 18-23 years. The results showed that the majority of respondents expressed their opinions on suitability and balance. With overall average was at a very Satisfied of 4.02. usefulness With overall average was at a high level of satisfaction, 3.90 in terms of aesthetics and suitability. The overall average was at the highest level of satisfaction, 4.07, With all three aspects were at the highest level of satisfaction.